Landslide hazard mapping in GIS (Journal of Nepal Geological Society, 2017)
Landslides are common geologic hazard occurring in all parts of the world predominantly in the rainy season. In recent years, landslide risk mapping has played an important role in developing land-use planning and it helps to minimize the loss of lives and damages to property. A variety of approaches have been used in landslide hazard and risk assessment and these can be classified into heuristic approach, statistical approach, deterministic approach, etc. An abrupt development of computers after 1990, geographic information systems (GIS) became essential tools for landslide hazard assessment. However, validation and replication is always difficult and there are little works on the satisfactory validation of various approaches. This paper deals with several aspects of landslide hazard and risk assessment by presenting a focalized review of GIS-based landslide hazard and risk assessment with a critical information of the state of the art in using GIS and digital elevation model (DEM) derivative for landslide hazard and risk assessment. This paper also describes some statistical and deterministic approaches and suggests detail step-by-step methodologies. It also describes in brief about integration of various database software and GIS.